2018
DOI: 10.1136/annrheumdis-2018-213217
|View full text |Cite
|
Sign up to set email alerts
|

The predictive role of ultrasound-detected tenosynovitis and joint synovitis for flare in patients with rheumatoid arthritis in stable remission. Results of an Italian multicentre study of the Italian Society for Rheumatology Group for Ultrasound: the STARTER study

Abstract: PD positivity in tendons and joints is an independent risk factor of flare in patients with RA in clinical remission. Musculoskeletal ultrasound evaluation is a valuable tool to monitor and help decision making in patients with RA in clinical remission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
47
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 79 publications
(52 citation statements)
references
References 36 publications
3
47
0
2
Order By: Relevance
“…US examination as a sensitive imaging technique for the detection of synovitis may be needed to determine imaging remission [39][40][41]. This is important as US-detected synovitis in clinical remission is a predictor for a relapse and loss of remission [9,10,42].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…US examination as a sensitive imaging technique for the detection of synovitis may be needed to determine imaging remission [39][40][41]. This is important as US-detected synovitis in clinical remission is a predictor for a relapse and loss of remission [9,10,42].…”
Section: Discussionmentioning
confidence: 99%
“…MSUS has been proved to be more sensitive than physical examination for the detection of synovitis [7]. Evidence exists that the presence of a power Doppler (PD) signal in RA patients in clinical remission predicts structural progression and a recent relapse [4,[8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…On one hand, the lack of ultrasound activity predicts achievement and persistence of remission (33,34). On the other hand, there is a very high degree of confidence that residual synovial activity is a significant predictor for loss of remission (relapse, flare) and radiographic progression since controlled studies (35)(36)(37), meta-analyses (38,39), magnetic resonance imaging (MRI) studies (40)(41)(42)(43)(44)(45)(46), biological markers (14) and histology (47,48) have confirmed the cited ultrasound observations. The loss of remission tends to happen in the first year of follow-up (39), especially if treatment is withdrawn (49,50).…”
Section: Introductionmentioning
confidence: 71%
“…Another study in RA patients with active disease and US-verified tenosynovitis reported that patient's VAS for tenosynovitis pain was responsive to treatment, parallel to improvement in US parameters, indicating that patients' pain perception may be triggered by tenosynovitis alone [34]. There is growing evidence that imaging-detected tenosynovitis has impact on RA diagnosing and prognostication of radiographic outcomes and prediction of clinical flares [35][36][37][38]. Our findings add to this evidence and lend support to the importance of tenosynovitis assessment at flares.…”
Section: Discussionmentioning
confidence: 99%